More than connectedness: Heterogeneity of CEO social network and firm value - Yiwei Fang; Bill Francis; Iftekhar Hasan (Bank of Finland, 2012)
This paper examines through various channels the effects of CEO social network heterogeneity on firm value. We construct four measures of heterogeneity based on demographic attributes, intellectual backgrounds, professional experience, and geographical exposures of individuals in the CEO social network. We find that CEO social network heterogeneity leads to higher Tobin's Q of firms. Greater CEO social network heterogeneity also leads to: (i) more innovation, (ii) more foreign sales growth, (iii) higher investment sensitivity to Tobin's Q, and (iv) better M&A performance. Overall, our results indicate that CEO social network heterogeneity is an aspect of CEO social capital and soft skills that deserves the attention of shareholders.
URN:NBN:fi:bof-20140807482
Keywords: G32; G30; D71; Z10; 330; CEO; social networks; corporate finance policy decisions; firm value